Patrimônio gastronômico de Pernambuco: memórias contemporâneas “desse povo coberto de glória”. - Calixto, Georgia Queiroga Capistrano (2025)
This study deals with the maintenance of culture through the transmission of knowledge and ways of doing things as an integral part of the intangible cultural heritage of the state of Pernambuco. Within a historical-cultural process, the work presents a vision that consecrates the transmission of ancestral cultures transmitted between generations as a way of preserving and perpetuating individual and collective flavors, stories and memories. It addresses aspects of the preparation, curiosities and customs related to cakes in the history of food, their reminiscences and evolution. It is entitled “Gastronomic Heritage of Pernambuco: contemporary memories of this “people covered in glory”” and highlights as a research problem the contribution of legal mechanisms to foster cultural apprehension and the consequent transmission of gastronomic traditions in a descriptive approach that seeks to qualitatively analyze the issue through the survey of bibliographic data and academic content, in addition to using the keywords “gastronomic heritage”, “memory” and “wedding cake” to delimit the theme. The main objective of this study is to analyze how the educational approach to gastronomic heritage contributes to encouraging the transmission and appreciation of these examples to future generations. To successfully address these issues, it seeks to identify, in three specific objectives, how strategies for recovering gastronomic memory and practices are passed down between generations, investigating whether legal mechanisms are capable of promoting the proper representation, safeguarding, and appreciation of this intangible heritage. It also aims to classify educational perspectives, combining gastronomic theory and practices with culture and memory, to preserve and give visibility to the state heritage collection among professionals, students, and enthusiasts of the topic at hand. In preparing this work, the author's experience in the gastronomic area was taken into account, as well as the narratives and family experiences of the pastry chefs in her family – the Queiroga Family – in the preparation and creation of examples of local gastronomy and confectionery, providing skill and affinities regarding the practices, procedures, and ways of making the highlighted examples. To conclude the research, a Gastronomic Cultural Catalog will be presented as a contribution to the dissemination, continuity and appreciation of flavors and knowledge of Pernambuco's gastronomic culture, highlighting the Pernambuco Wedding Cake, its recognition and registration as Intangible Cultural Heritage of the State of Pernambuco.